Corona politics: The cost of mismanaging pandemics - Helios Herrera; Maximilian Konradt; Guillermo Ordo\~nez; Christoph Trebesch (Kiel Institute for the World Economy (IfW), 2020)
The Covid-19 pandemic is a major test for governments around the world. We study the political consequences of (mis-)managing the Covid crisis by constructing a highfrequency dataset of government approval for 35 countries. In the first weeks after the outbreak, approval rates for incumbents increase strongly, consistent with a global 'rally around the flag' effect. Approval, however, drops again in countries where Covid cases continue to grow. This is especially true for governments that do not implement stringent policies to control the number of infections. Overall, the evidence suggests that loose pandemic policies are politically costly. Governments that placed more weight on health rather than short-term economic outcomes obtained higher approval.
Keywords: D72; H12; F50; 330; Political Popularity; Political Economy; Crisis Management; Covid-19